Risk factors of bloating and its association with common gastrointestinal disorders in a sample of Iranian adults - Hassanzadeh Keshteli, Ammar; Daneshpajouhnejad, Parnaz; Adibi, Peyman (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Bloating is an unpleasant but common gastrointestinal symptom that is experienced by many people at some stage in their lives. The current survey was conducted to investigate the epidemiology and risk factors of bloating and functional bloating (FB). In addition, we aimed to assess the association between bloating and functional gastrointestinal disorders (FGIDs). Materials and Methods: In this cross-sectional study, the self-administered modified Rome III questionnaire was used to assess gastrointestinal symptoms and FGIDs. Severity of bloating, demographic and anthropometric measurements, physical activity level, psychological distress, and depression and anxiety were also assessed. Results: Among the 4763 participants, 52.9% reported having experienced bloating at least occasionally in the past three months (among which 14.1% had severe or very severe symptoms); 19.7% of subjects were found to have FB. After adjusting for multiple variables, female gender, university degree, obesity, and anxiety were associated with both bloating and FB, while depression and psychological distress were only associated with bloating. The positive predictive value and negative predictive value of bloating for the diagnosis of functional bowel disorder were 92.9% and 80.1%, respectively. Conclusion: Bloating and FB are highly prevalent in the study population. We also identified several demographic, psychological, and lifestyle-related risk factors of bloating in this population.